CSC248: Fundamentals of Data Structures / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course provides the concept of information organization and manipulation in a computer to emphasize the use of the data structure in problem solving. An object-oriented approach will be used to develop the programming solutions.